Translation, cross-cultural adaptation, and validation of the Leuven Knowledge Questionnaire for congenital heart disease instrument into Brazilian Portuguese - Fátima Helena Cecchetto; Giuseppe Dick Bonato; Thaís Sena Mombach Barreto; Fernando Riegel; Lúcia Campos Pellanda (Elsevier, 2021)
Objective: To translate the Leuven Knowledge Questionnaire for Congenital Heart Disease into Brazilian Portuguese and to validate its psychometric properties with parents and family caregivers of children with congenital heart disease. Method: This was a six-step methodological study, including the translation, synthesis, back-translation, evaluation of the version translated by the committee of experts, pre-testing, and validation, for which two pilot tests were used including the think-aloud protocol. The content validity index and the frequency of socioeconomic data were calculated in a statistical programming environment. Results: In content validation, the instrument showed good applicability among experts, with average content validity index of 0.8-1, while kappa agreement analysis was between 0.76 to 1; both results were considered adequate for validation. Conclusions: The results suggest reliability among the evaluators, indicating the instrument's accuracy and the possibility of using it to assess the knowledge of parents and family caregivers about congenital heart disease.